Frontispiece: Luminescent Gold Nanorods To Enhance the Near‐Infrared Emission of a Photosensitizer for Targeted Cancer Imaging and Dual Therapy: Experimental and Theoretical Approach. Issue 13 (2nd March 2020) - Nair, Resmi V.; Nair, Lakshmi V.; Govindachar, Divya Maldepalli; Santhakumar, Hema; Nazeer, Shaiju S.; Rekha, Charuvil Radhakrishnapillai; Shenoy, Sachin J.; Periyasamy, Ganga; Jayasree, Ramapurath S.
Abstract : Dear cancer cells, we don't want you … Plasmonic photothermal therapy of gold nanorods and porphyrin‐induced photodynamic therapy, in combination, attack cancer cells to destroy them. The enhanced fluorescence of protoporphyrin IX in the near‐IR region facilitated by competitive charge transfer from plasmonic nanoparticles is used to see the cancer cells. The multifunctional system targets only cancer cells for near‐IR imaging and multiple therapy both in vitro and in vivo. For more details, see the Full Paper by G. Periyasamy, R. S. Jayasree and co‐workers on page 2826 ff.